Homo inc.orporated : le triangle et la licorne qui pète - Bourcier, Sam (M.H) (Cambourakis, 2017)
Avec Homo Inc.orporated, Sam Bourcier poursuit la réflexion menée dans la trilogie des Queer Zones. Mariage, procréation, travail, patrie, les gais et les lesbiennes ont basculé dans la sphère de la reproduction et de la production. Que reste-t-il du sujet politique LGBT lorsqu'il est défini par le droit et le management de la diversité ? Pas grand-chose. Raison pour laquelle les queers et les transféministes se mobilisent pour un agenda de redistribution économique et de justice sociale plus large que la simple demande d'égalité et d'intégration. Homo Inc.orporated propose une critique radicale de l'homonationalisme et des politiques de l'égalité des droits. C'est aussi une boîte à outils pour lutter contre le néolibéralisme, avec une réflexion et de nouveaux moyens d'action sur les politiques du savoir à l'université, le genre comme travail, la grève du genre sans oublier le gender fucking !
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; cours; europe; fem1000; france; identités LGBTQIA2+; justice sociale; militance; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; thématiques; transféminisme

« Queer », « transpédégouine », « torduEs », entre adaptation et réappropriation, les dynamiques de traduction au cœur des créations langagières de l’activisme féministe queer - Lorenzi, Marie-Émilie (GLAD!Revue sur le langage, le genre et les sexualités, 2017)
S’il ne fait aucun doute que les activistes féministes queer ont pu reprendre à leur compte le slogan « mon corps est un champ de bataille », elles et ils n’en ont pas pour autant négligé d’investir le langage, ce champ de bataille symbolique. Intervenir sur la langue, se réapproprier les discours de haine en les détournant, sont alors autant de stratégies contre-discursives participant activement au processus de subjectivation. Les enjeux de langage deviennent ainsi un terrain propice pour appréhender le monde, élaborer un espace commun, intelligible et safe, et se constituer en tant que sujet. Ils participent pleinement à l’élaboration politique, identitaire et culturelle de la mouvance ou praxis féministe queer en France. Cette analyse cherche à examiner les dynamiques de traduction au cœur des créations langagières des activistes féministes queer, notamment celles qui relèvent des questions d’autodéfinition. Bien plus qu’une simple formalité de transcription langagière, la traduction soulève des enjeux politiques et culturels déterminants. À partir d’une lecture contextualisée et au plus près des usages, il s’agit ici de souligner l’ambivalence et la complexité de tout processus de traduction, oscillant entre circulation et déformation, réappropriation et reconfiguration.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; communication inclusive; cours; discipline; europe; fem1000; france; identités LGBTQIA2+; langage; pratiques féministes; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; traduction

A messy trajectory: From medical sociology to crip theory - Egner J. (Research in Social Science and Disability ; 9, 2016)
Purpose The purpose of this paper is to draw attention to the work of sociologists who laid the foundation for queer and crip approaches to disability and to address how queer and crip theory has and can help to re-conceptualize our understandings of health, illness, disability, and sexuality. Methodology/approach This paper is an examination of historical moments and prominent literature within medical sociology and sociology of disability. Sociological and popular understandings of disability and sexuality have often mirrored each other historically. Although this literature review focuses primarily on medical sociology and disability studies literature, some works of scholars specializing in gender studies, sexuality, literature, history, and queer studies are also included Findings In this paper, I argue that the medicalization and pathologization of human differences specifically as it pertains to sexuality and disability within the medical sociological literature have led to constructionist, social model, and feminist critiques. It is these critiques that then laid the foundation for the development of queer and crip theoretical approaches to both disability and sexuality. Originality/value Crip and queer approaches to disability provide a clear call for future sociological research. Few social science scholars have applied queer and crip approaches in empirical studies on disability. The majority of work in this area is located in the humanities and concerned with literary criticism. A broader array of empirical work on the intersection of sexuality and disability from queer/crip perspectives is needed both to refine these postmodern theoretical models and to examine their implications for the complex lived experience that lies at the intersection of sexuality and disability. In queering disability and cripping sexuality and gender, we may be able not only to more fully conceptualize disability, sexuality, and gender as individual social categories, but also to more fully understand the complex intersection of these social locations.
Keywords: EDI; approches et analyses; care; cours; crip; discipline; histoire et politique; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sociologie; sofia; thématiques

Intersex Initiative: From "Intersex" to "DSD" - Koyama, Emi (2006)
keynote speech presented at Translating Identity conference held at University of Vermont in February 2006.
Keywords: EDI; LGBTQIA2+; approches et analyses; capacitisme; cours; discipline; intersexuation; patriarcat; premier cycle; queer; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap

Crip theory: cultural signs of queerness and disability - MacRuer, Robert (New York University Press, 2006)
A bold and contemporary discourse of the intersection of disability studies and queer studies Crip Theory attends to the contemporary cultures of disability and queerness that are coming out all over. Both disability studies and queer theory are centrally concerned with how bodies, pleasures, and identities are represented as “normal” or as abject, but Crip Theory is the first book to analyze thoroughly the ways in which these interdisciplinary fields inform each other. Drawing on feminist theory, African American and Latino/a cultural theories, composition studies, film and television studies, and theories of globalization and counter-globalization, Robert McRuer articulates the central concerns of crip theory and considers how such a critical perspective might impact cultural and historical inquiry in the humanities. Crip Theory puts forward readings of the Sharon Kowalski story, the performance art of Bob Flanagan, and the journals of Gary Fisher, as well as critiques of the domesticated queerness and disability marketed by the Millennium March, or Bravo TV’s Queer Eye for the Straight Guy. McRuer examines how dominant and marginal bodily and sexual identities are composed, and considers the vibrant ways that disability and queerness unsettle and re-write those identities in order to insist that another world is possible.
Section: 283 pages : illustrations
Keywords: EDI; LGBTQIA2+; approches et analyses; art; cours; crip; discipline; militance; premier cycle; queer; santé; soc2014; thématiques; études critique du handicap; études littéraires

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Integrating Disability, Transforming Feminist Theory - Garland-Thomson, Rosemarie (NWSA Journal, 2002)
This essay aims to amplify feminist theory by articulating and fostering feminist disability theory. It names feminist disability studies as an academic field of inquiry, describes work that is already underway, calls for needed study and sets an agenda for future work in feminist disability studies. Feminist disability theory augments the terms and confronts the limits of the ways we understand human diversity, the materiality of the body, multiculturalism, and the social formations that interpret bodily differences. The essay asserts that integrating disability as a category of analysis and a system of representation deepens, expands, and challenges feminist theory. To elaborate on these premises, the essay discusses four fundamental and interpenetrating domains of feminist theory: representation, the body, identity, and activism, suggesting some critical inquiries that considering disability can generate within these theoretical arenas.
Keywords: EDI; activisme; approches et analyses; corps; cours; discipline; militance; premier cycle; queer; ressource en ligne; santé; sciences humaines; sciences sociales; sex1920; thématiques; études critiques du handicap; études féministes